Sistem Informasi Pemasaran, Penjualan, dan Penyewaan Mobil Berbasis Laravel di Batam - Marcellinton Marcellinton; Sasa Ani Arnomo (Universitas Putera Batam, 2025)
This system is designed to facilitate interaction between sellers, renters, and buyers of vehicles through an efficient, transparent, and easily accessible platform. The system development uses the Agile Development method, which allows development to be carried out in stages by involving user feedback at every stage. The main features of the system include vehicle search with dynamic filters, user rating and review systems, live chat between sellers and buyers, and a wishlist of vehicles. System testing was carried out using the Black-Box Testing method, which showed that all features functioned according to the designed specifications. The results of the study showed that this system succeeded in increasing the efficiency of the transaction process, providing better transparency, and strengthening trust between users. Web-based, this system can be accessed anytime and anywhere, so that it can reach more users and increase interaction. With proper implementation, this system is expected to be an effective solution to facilitate marketing, sales, and rental of vehicles in Batam City.